The role of LANP and ataxin 1 in E4F-mediated transcriptional repression - Cvetanovic, Marija (Nature Publishing Group, 2007)
The leucine-rich acidic nuclear protein (LANP) belongs to the INHAT family of corepressors that inhibits histone acetyltransferases. The mechanism by which LANP restricts its repression to specific genes is unknown. Here, we report that LANP forms a complex with transcriptional repressor E4F and modulates its activity. As LANP interacts with ataxin 1—a protein mutated in the neurodegenerative disease spinocerebellar ataxia type 1 (SCA1)—we tested whether ataxin 1 can alter the E4F–LANP interaction. We show that ataxin 1 relieves the transcriptional repression induced by the LANP–E4F complex by competing with E4F for LANP. These results provide the first functional link, to our knowledge, between LANP and ataxin 1, and indicate a potential mechanism for the transcriptional aberrations observed in SCA1.